Heat Stress Increases Movement Jerk During Physical Exertion - Hostler, David; Schwob, Jacqueline; Schlader, Zachary J.; Cavuoto, Lora (Frontiers in Physiology, 2021)
Objective: Movement efficiency can be quantified during physical tasks by measuring the rate of change of acceleration (jerk). Jerk captures the smoothness of a motion and has been used to quantify movement for upper extremity and torso-based tasks. We collected triaxial accelerometer data during four physical tasks commonly performed in the work place to determine if jerk increases with physiologic strain. Methods: Participants completed a circuit of activities that mimicked the demands of manual labor in hot (40 ºC) and temperate (18 ºC) conditions. The circuit included walking on a treadmill carrying a load on the shoulder, lifting objects from the floor to the table, using a dead blow to strike the end of a heavy steel beam, and a kneeling rope pull. After the 9 min circuit, the participant had a standing rest for 1 min before repeating the circuit 3 additional times. Participants were instrumented with four 3-axis accelerometers (Actigraph wGT3X) secured to the torso, wrist, and upper arm. Results: There were 20 trials in the hot condition and 12 trials in the temperate condition. Heart rate and core body temperature increased during both protocols (p<0.001). Measures of jerk varied by accelerometer location and activity. During treadmill walking, the wrist, torso, arm accelerometers measured higher jerk during the fourth circuit in the hot condition. During the lifting task, mean jerk increased in the hot condition in all accelerometers. Max jerk increased in the temperate condition in the arm accelerometer and jerk cost increased in the hot condition in the torso and arm accelerometers. Conclusions: Forty minutes of paced work performed in the heat resulted in increased acceleration and jerk in accelerometers placed on the torso, arm, and wrist. The accelerometers most consistently reporting these changes were task specific and suggest that a limited number of worn sensors could identify the onset of fatigue and increased injury risk.